Propuesta gastronómica para la elaboración de productos a base de zapallo para los adultos mayores del “Hogar de Ancianos Instituto Estupiñán” del cantón Latacunga provincia de Cotopaxi 2012 - Chuquitarco Rueda, Welinton Omar (2013)
This research has a descriptive design and a transversal study. Its objetive is to present a Gastronomic proposal for the elaboration of pumpkin products for the senior citizens from the Estupiñán Institute Elderly Home, in the city of Latacunga, Cotopaxi province. The goal is to determine pumpkin (ripe and unripe) organoleptic features in new preparations to check acceptability and to include them in their daily menu. Interviews were conducted to a total universe of 70 elderly people. From the obtained results, the acceptability percentage has been determined according to its color, taste, smell, and visual presentation in the different dishes detailed as follows: Concerning soups (made with unripe pumpkin): 89% acceptance corresponds to soup cream, 94% to thick soup, 88% to parboiled soup, and 87% to regular soup. With reference to salads:89% corresponds to salad 1, 84% to salad to salad 2, 83%to salad 3, and 82% to salad 4. Regarding garnishing:85% corresponds to a soufflé, 86% to mashed pumpkin, 86% to stew, and 94% to a salt cake. In relation to desserts (ripe pumpkin): 97% corresponds to a pumpkin pie,94% to a sweet pumpkin cake, 94% to pumpkin syrup, and 85% to pumpkin cookies. It is recommended to include these new preparations made with ripe and unripe pumpkin in the menu since this is a traditional element which has important nutrients and multiple benefits for the elderly daily food.